2019
DOI: 10.26850/1678-4618eqj.v44.4.2019.p11-26
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of caffeine in wastewater and sewage and applied techniques for analysis: a review

Abstract: Emerging contaminants are substances found in the environment whose concentrations vary from µg to ng L-1 and whose presence in wastewater has gained popularity in the scientific community due to the potential impacts these compounds can cause to the environment. This designation concerns the lack of legislation to regulate their discharge or even to monitor these compounds. Moreover, emerging contaminants are capable of causing harmful effects to nontarget organisms and therefore affect the ecosystem balance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…It has also been reported that about 4000 different pharmaceutical compounds entered environmental compartments in Europe (Mompelat et al 2009 ). However, the detection of these emerging contaminants from various environmental compartments and their further retrieval, especially via the conventional wastewater treatment plants have always been a challenging task due to their low concentrations, typically in the range of microgram/l to nanograms/l (Adelodun et al 2021a , b , c , d ; Marasco Júnior et al 2019 ; Snyder et al 2007 ; Zhang et al 2021 ). Even though they appear at very low concentrations in environmental compartments or reclaimed wastewaters, the physicochemical properties and toxicological effects of the compounds of PPCPs are found to have negative effects on the biotic environment, including the development, growth, and reproduction of biota (Ajibade et al 2021a , b ; Cheng et al 2021 ; Zhang et al 2021 ).…”
Section: Detection Determination and Extraction Methodsmentioning
confidence: 99%
“…It has also been reported that about 4000 different pharmaceutical compounds entered environmental compartments in Europe (Mompelat et al 2009 ). However, the detection of these emerging contaminants from various environmental compartments and their further retrieval, especially via the conventional wastewater treatment plants have always been a challenging task due to their low concentrations, typically in the range of microgram/l to nanograms/l (Adelodun et al 2021a , b , c , d ; Marasco Júnior et al 2019 ; Snyder et al 2007 ; Zhang et al 2021 ). Even though they appear at very low concentrations in environmental compartments or reclaimed wastewaters, the physicochemical properties and toxicological effects of the compounds of PPCPs are found to have negative effects on the biotic environment, including the development, growth, and reproduction of biota (Ajibade et al 2021a , b ; Cheng et al 2021 ; Zhang et al 2021 ).…”
Section: Detection Determination and Extraction Methodsmentioning
confidence: 99%
“…Analytical techniques using mass spectrometers such as Orbitrap, quadrupole (Q) with linear ion-trap (QTRAP), and Q with time-of-flight (QToF) enabled the detection of compounds with extremely low concentrations (pg/L to µg/L ranges). Since 2006, a huge leap in the number of publications and abstracts presented in different scientific platforms was observed alongside the development of advanced detection schemes for PPCPs [21,22].…”
Section: Trends In Ppcp Researchmentioning
confidence: 99%
“…Due to their high solubility and low volatility, caffeine is quite persistent in water bodies [3]. These characteristics allow caffeine detection in the environment which are essential to correlate the risk it may offer to humans and ecosystems [4][5][6][7], and its presence in environmental matrices were confirm in recent studies [8]. Per example, wastewater from two WWTPs in Barbados, a city with about 300,000 inhabitants, were analyzed and it was obtained a range of caffeine concentrations from 0.10 to 6.90 μg L −1 [9]; in Italy, 13 WWTPs located in northern, central, and southern (responsible for the collection and treatment of effluents from 50 to 500,000 inhabitants) were evaluated and the results showed caffeine concentrations between 17.6 and 67.6 μg L −1 [10].…”
Section: Introductionmentioning
confidence: 99%